Solusi Pengolahan Limbah di Kota Padangsidimpuan - Indra Hadinata Rambe; Husniah Ramadhani Pulungan (Marpokat: Jurnal Pengabdian Kepada Masyarakat, 2023)
Waste is a substance produced from an industrial and household. Waste can be in the form of garbage, latrine water (black water), and waste water from various other domestic activities, waste treatment can also produce economic value and solve waste problems. The purpose of this study was to determine the waste treatment system of the city of Padang Sidempuan, North Sumatera Province by using the data obtained and bibliography searches related to this writing. The type of research used by the author is descriptive, namely to explain about the waste management system in the city of Padang Sidempuan. While the data taken in this study is primary data obtained based on direct observation, namely by looking at places that have been affected by flooding and pre-existing hygiene data.